A new peirosaurid (Crocodyliformes, mesoeucrocodylia) from the Upper Cretaceous of Patagonia, Argentina - Barrios, Francisco (2016)
Fil: Barrios, Francisco. Museo Municipal Carmen Funes. Plaza Huincul. Neuquén; Argentina